PERBEDAAN MOTIVASI BELAJAR SEKOLAH SHIF PAGI, SHIF SIANG, DAN SHIF SORE DI UPTD SMP NEGERI 20 KOTA KUPANG - Siagian, Fera Ratna Dewi; Maria Andriani Barek Ladjar; Silaban , Ricky Alfredo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the differences in students’ learning motivation among those who attend classes in the morning shift, afternoon shift, and evening shift at UPTD SMP Negeri 20 Kupang City. The background of this research is based on the shift-based learning system implemented in the school to address the limitations of classroom space and the increasing number of students. Differences in learning time are assumed to influence students’ physical and psychological conditions, as well as their level of readiness to participate in the learning process, which ultimately affects their learning motivation. This study employed a quantitative approach using a comparative method. The research subjects were students who participated in learning activities in three shifts, namely the morning shift, afternoon shift, and evening shift, totaling 127 students. The sampling technique used was proportional random sampling, resulting in a sample of 90 students. Data collection was carried out using a learning motivation questionnaire that had been tested for validity and reliability. The collected data were then analyzed using comparative statistical analysis to determine differences in the level of learning motivation among the shift groups. The results of the study indicate that there are differences in the level of learning motivation among students who attend classes in the morning, afternoon, and evening shifts. In general, students who study in the morning shift tend to have higher learning motivation compared to those in the afternoon and evening shifts. This condition is influenced by students’ fresher physical condition, better concentration, and a more conducive learning environment in the morning. Meanwhile, students in the afternoon and evening shifts tend to show relatively lower levels of motivation due to factors such as fatigue, environmental temperature, and prior activities.